Observation of long-range, near-side angular correlations in proton-proton collisions at the LHC - Khachatryan, V. (2010)
Results on two-particle angular correlations for charged particles emitted in proton-proton collisions at center-of-mass energies of 0.9, 2.36, and 7TeV are presented, using data collected with the CMS detector over a broad range of pseudorapidity (eta) and azimuthal angle (phi). Short-range correlations in Delta(eta), which are studied in minimum bias events, are characterized using a simple independent cluster parametrization in order to quantify their strength (cluster size) and their extent in eta (cluster decay width). Long-range azimuthal correlations are studied differentially as a function of charged particle multiplicity and particle transverse momentum using a 980 nb(-1) data set at 7TeV. In high multiplicity events, a pronounced structure emerges in the two-dimensional correlation function for particle pairs with intermediate p(T) of 1-3 GeV/c, 2.0 <vertical bar Delta(eta)vertical bar < 4.8 and Delta phi approximate to 0. This is the first observation of such a long-range, near-side feature in two-particle correlation functions in p p or p (p) over bar collisions.